Relationship between Atherogenic Index of Plasma with HbA1c Levels in Type 2 Diabetes Mellitus Patients - Ni Putu Sukma Sumantri Prabandari; Ida Ayu Putri Wirawati; Ni Nyoman Mahartini (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2021)
Type 2 Diabetes Mellitus (T2DM) is a global health problem due to an increasing prevalence and incidence. HbA1c as aparameter for glycemic control is still above the desired target of 7%. Atherogenic Index of Plasma (AIP) is predicted to be anindicator of cardiovascular disease risk in T2DM. Dyslipidemia in T2DM patients showed a result of increased triglycerideand decreased HDL cholesterol levels. This study aimed to determine the relationship between HbA1c and AIP, triglycerides,and HDL cholesterol in T2DM patients. An analytical observational study using a cross-sectional method on 74 DMT2patients who underwent HbA1c and lipid profile examinations in January-March 2020. Atherogenic index of plasma wascalculated by the logarithmic equation (triglycerides/HDL cholesterol). Data were analyzed by SPSS 25.0. The relationshipbetween HbA1c with AIP, triglycerides, and HDL cholesterol using the Pearson correlation test. Atherogenic index of plasma(0.25±0.25) and triglycerides (211.92±146.09 mg/dL) were found to be higher in the poor glycemic control group (HbA1c> 7%) than AIP (-0.04±0.20) and triglycerides (108.96±38.96 mg/dL) in the good glycemic control group (p < 0.05). HDLcholesterol (40.08±12.64 mg/dL) was found to be higher in the poor glycemic control group than HDL cholesterol(52.28±18.12 mg/dL) in the good glycemic control group (p < 0.05). There was a significant positive correlation betweenHbA1c and AIP (r=0.411, p=0.000), HbA1c with triglycerides (r=0.418, p=0.000), and a significant negative correlationbetween HbA1c and HDL cholesterol (r=-0.233, p=0.046). Insulin resistance can cause lipid metabolism disorders,inflammation, oxidative stress, and coagulation disorders. Maintaining glycemic control and lipid control plays an importantrole in preventing diabetes complications. There is a significant positive correlation between HbA1c and AIP, HbA1c andtriglycerides, and a significant negative correlation between HbA1c and total cholesterol in T2DM patients.